2005
DOI: 10.1523/jneurosci.1796-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Signals in the Monkey Basolateral Amygdala during Reward Schedules

Abstract: The amygdala is critical for connecting emotional reactions with environmental events. We recorded neurons from the basolateral complex of two monkeys while they performed visually cued schedules of sequential color discrimination trials, with both valid and random cues. When the cues were valid, the visual cue, which was present throughout each trial, indicated how many trials remained to be successfully completed before a reward. Seventy-six percent of recorded neurons showed response selectivity, with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
76
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 51 publications
16
76
1
Order By: Relevance
“…S3), and many choice-predictive neurons did not track them (SI Results). Third, a previous study showed that reward expectation-related activity in amygdala neurons covaried with the temporal distance to reward receipt (24). By contrast, activity in many choice-predictive neurons in the present study did not covary with distance to reward (SI Results).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…S3), and many choice-predictive neurons did not track them (SI Results). Third, a previous study showed that reward expectation-related activity in amygdala neurons covaried with the temporal distance to reward receipt (24). By contrast, activity in many choice-predictive neurons in the present study did not covary with distance to reward (SI Results).…”
Section: Discussioncontrasting
confidence: 70%
“…S7). We were unable to identify systematic differences between recording sites (nonsignificant χ 2 tests); therefore, in line with previous studies (6,24), we present the neuronal data as one set.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, posterior orbitofrontal areas target dual systems in the amygdala that can potentially increase or decrease autonomic drive, activated perhaps according to the emotional significance of the situation or environment (Ghashghaei and Barbas, 2002;Barbas et al, 2003;Arana et al, 2003;Sugase-Miyamoto and Richmond, 2005;Wellman et al, 2005;Paton et al, 2006). Decision for action based on the significance of the environment is a complex process that likely involves many structures, including communication between caudal lateral prefrontal cortices, which are thought to have executive functions, and orbitofrontal and medial prefrontal cortices associated with processing the value of stimuli [(Wallis and Miller, 2003;PadoaSchioppa and Assad, 2006); reviewed in (Miller and Cohen, 2001)].…”
Section: Sequence Of Information Processing For Emotionsmentioning
confidence: 99%
“…That is, monkeys get the reward whether or not lipping occurs. In earlier studies conducted in this laboratory, licking responses were monitored in monkeys performing the same reward schedule task with the spout being positioned outside of the monkey's mouth (Sugase-Miyamoto and Richmond 2005). In those conditions, cueevoked licking was stronger in rewarded trials of the schedules.…”
Section: Operant and Instinctive Behaviors In The Reward Schedulesmentioning
confidence: 99%